Measuring the Impact of Social Program: A Case of BTTM Indonesia - Slamet, Aam; Haris, Abdul (SMART Insight, 2023)
This research focuses on exploring social values through Social Return on Investment (SROI) analysis in the evaluation of the BTTM Tazkia Bogor Holistic Development Project. Qualitative methods are used to analyze the social impacts produced by these projects. The SROI approach is applied using in-depth interviews as the main data collection tool. The results of the SROI analysis reveal a ratio of 1:6.43 which indicates that every investment worth Rp 1 generates a social impact worth Rp 6.43. These findings illustrate the significant positive impact of this program in creating social value in various aspects. This program not only provides financial value beyond the initial investment, but also has a profound positive influence in aspects such as financial, social, and spirituality. As research implications, these results can be used in designing, managing, and measuring the impact of similar programs in the future, as well as encouraging a broader understanding of the social value created by organizations in the context of sustainable development.